EVALUATION OF PHISHING DETECTION ATTACKS WITH URL COMPOSITION - Patel, Ravindra; Patidar, Mr.Kailash; Lohiya, Harsh (IJRDO -Journal of Computer Science Engineering, 2016)
Rapid increase in the size of web users. Users enter sensitive information such aspasswords, their personal and professional information into scam web sites. Phishing is thecriminally fraudulent process of attempting to acquire sensitive information such as usernames,passwords and credit card details, for some illegitimate purpose. Such scam sites cause substantialdamages to individuals and corporations. These attacks can be analyzed through this work, and aplug in is designed which provide security from the fake websites . This work is improved by usingdecision tree c4.5 over id3 and a comparison is drawn.